2010
DOI: 10.1111/j.1741-3729.2010.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy of Young Adults: The Importance of Parental Socialization

Abstract: This article tests a conceptual model of perceived parental influence on the financial literacy of young adults. Structural equation modeling was used to test whether (a) parents were perceived to influence young adults' financial knowledge, attitudes, and behaviors and (b) the degree to which young adults' financial attitudes mediated financial knowledge and perceived parental influence on young adults' financial behaviors. A sample consisting of 420 college students participated in the study. Findings by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
308
3
22

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(359 citation statements)
references
References 22 publications
26
308
3
22
Order By: Relevance
“…In another study, Hancock, Jorgensen, and Swanson (2012) used data collected from 413 students in seven universities in the USA and found that students who were juniors or seniors, who had parents arguing about finances at home and who were comfortable making the minimum payments were more likely have higher levels of credit card debt. Using the same dataset, Jorgensen and Savla (2010) found that parental influence had an indirect effect on the financial behaviors of college students mediated through financial attitudes. The importance of parental involvement for credit card behaviors of college students was also confirmed by Palmer, Pinto, and Parente (2001) who used data from a sample 355 college students in the USA and showed that parental involvement prior to the acquisition of the credit card reduces students' outstanding card debt while post-acquisition involvement has the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Hancock, Jorgensen, and Swanson (2012) used data collected from 413 students in seven universities in the USA and found that students who were juniors or seniors, who had parents arguing about finances at home and who were comfortable making the minimum payments were more likely have higher levels of credit card debt. Using the same dataset, Jorgensen and Savla (2010) found that parental influence had an indirect effect on the financial behaviors of college students mediated through financial attitudes. The importance of parental involvement for credit card behaviors of college students was also confirmed by Palmer, Pinto, and Parente (2001) who used data from a sample 355 college students in the USA and showed that parental involvement prior to the acquisition of the credit card reduces students' outstanding card debt while post-acquisition involvement has the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kennedy (2013), as researchers have suggested that those with a lack of financial literacy possess greater sums of credit card debt (Chudry et al, 2011;Grable et al, 2009), it is conceivable that financial literacy be a causal factor in determining the behavioral intention to use credit cards and acquire credit card debt. Furthermore, recent researchers have identified a significant relationship between financial literacy and credit card debt (Chudry et al, 2011;Grable et al, 2009;Hayes, 2012;Jorgensen & Savla, 2010). This suggests that financial literacy is not only conceivable but empirically supported as a causal factor in determining actual credit card debt.…”
Section: Financial Literacymentioning
confidence: 99%
“…Financial literacy measures a specific construct that has been widely studied within the broad field of social science: including psychology, economics and sociology (Chudry, Foxall, & Pallister, 2011;Grable, Park, & Joo, 2009;Hayes, 2012;Jorgensen & Savla, 2010). In considering these factors, financial literacy meets all of Ajzen (2008) criteria for being added as a predictor.…”
Section: Financial Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…For individuals with successful siblings, the siblings were also a significant influence on retirement decisions. Prior research also showed that discussing financial issues with parents had a positive influence on likelihood of saving for retirement among young people (Hancock et al, 2013;Jorgensen and Savla, 2010;Mandell, 2009;Sabri et al 2010).…”
Section: Family Influencesmentioning
confidence: 99%